Radiographic appearance of susuk in the facial region: a systematic review - Ghazali, Ahmad Badruddin; Abdullah Thaidi, Nur Imanina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
The purpose of this study was to integrate the available data published to date on susuk or charm needles into a comprehensive analysis of their clinical/radiological features. An electronic search was undertaken in September 2019. Eligibility criteria included publications having enough clinical and radiological to confirm a definite diagnosis. The initial literature search resulted in 48 publications. Ten publications were excluded for duplicates, and another 17 excluded after a screening of the abstract. Besides, the screening of the abstract shows that five publications were not meeting the inclusion criteria, resulting in a total of 14 publications of susuk that were included in the systematic review. Bias analysis was conducted according to Oxford Center for Evidence-Based Medicine. The resulting total of 78 cases from the selected publications were analysed, showing a wide age range with different distribution among gender and ethnicity. Three cases reported in the literature having symptoms related to susuk. Susuk can be seen as an incidental finding during a routine radiographic assessment, and clinicians should be able to differentiate it from other radiopaque foreign bodies. The practice is not limited to South East Asian population and can be seen in wide racial profiles.